KEEFEKTIFAN KALIMAT DALAM KARANGAN EKSPOSISI SISWA KELAS VIII SMPN 1 BATANG ANAI - Saputra, Romi; Ermanto, Ermanto; Gani, Erizal (Universitas Negeri Padang, 2016)
ABSTRACT This research was conducted based on too many uses of ineffective sentences in the exposition essays written by the second gtade students of Batang Anai Junior High School. There were three purposes of this research, which were to describe the effectiveness of sentences written by the second grade students of Batang Anai Junior High School based on first sentence structure, second diction, and third words spelling. This research was a qualitative research. The method used in this research was descriptive. The results of the research were from 132 sentences used as the research data, there were 5 effective sentences and 127 ineffective sentences. In short, there were 12 ineffective sentences of the structure aspect, 85 ineffective sentences of the diction aspect, and 101 ineffective seiltences of the words spelling aspect.Â Kata kunci : keefektifan, kalimat, karangan, eksposisi, siswa